NKG2D signaling is coupled to the interleukin 15 receptor signaling pathway - Horng, T; Bezbradica, J; Medzhitov, R (Springer Nature, 2007)
The effector functions of natural killer cells are regulated by activating receptors, which recognize stress-inducible ligands expressed on target cells and signal through association with signaling adaptors. Here we developed a mouse model in which a fusion of the signaling adaptor DAP10 and ubiquitin efficiently downregulated expression of the activating receptor NKG2D on the surfaces of natural killer cells. With this system, we identified coupling of the signaling pathways triggered by NKG2D and DAP10 to those initiated by the interleukin 15 receptor. We suggest that this coupling of activating receptors to other receptor systems could function more generally to regulate cell type–specific signaling events in distinct physiological contexts.